Studi Eksperimental Karakteristik Laju Aliran Kalor Material Karbon Aktif Bambu Betung Dengan Holding Time 30 Menit Sebagai Material Pad Alternatif - Palindangan, Novry F; Wijaksana, Hendra; Prananda Surya, I Gede Teddy (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract As time goes by, the development of increasingly advanced technology, the application of refrigeration has been widely applied as we can apply it in everyday life, namely the use of air conditioning, but excessive use of air conditioning can release waste substances in the form of freon which has a negative effect on the environment. We need a cooling system that is energy efficient and environmentally friendly such as an evaporative cooling system that uses a cooling process by directly contacting the incoming air with the air so that heat flows from the air to the air which results in the evaporation process of the pad material that has previously been moistened by air, the pad material This is a cooling medium that comes from local Balinese bamboo, namely Betung Bamboo. In this study, using bamboo activated carbon as a pad material to determine the heat flow rate in a direct evaporative cooling system with carbonization temperatures of 400 oC, 500 oC, 600 oC, 700 oC, 800 oC and activated at a temperature of 600 oC with a holding time of 30 minutes. The results of the tests that have been carried out show that the KARV 800 specimen with the highest mass flow rate of 2.84x10-8 kg/s produces the highest heat rate of 0.0640 Watt which can be used as potential in the manufacture of new pad materials in the direct evaporative cooling system. Keywords: direct evaporative cooling, bamboo betung, carbonization, activation, mass flow rate, heat flow rate.